2019
DOI: 10.1097/pcc.0000000000001939
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Recurrent Acute Kidney Injury in Children Who Undergo Multiple Cardiac Surgeries: A Retrospective Analysis

Abstract: Objective: Determine the risk factors for repeated episodes of acute kidney injury (AKI) in children who undergo multiple cardiac surgical procedures Design: Single center retrospective chart review Setting: Cardiac intensive care unit at a quaternary pediatric care center Patients: Birth to 18 years who underwent at least 2 cardiac surgical procedures with cardiopulmonary bypass. Interventions: None Measurements and Main Results: 180 patients underwent 2 cardiac surgical procedures and 89 underwent 3. AKI was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…A recent study by Hasson et al looked at a heterogeneous population of pediatric congenital heart disease patients undergoing multiple surgeries. In their cohort, odds of acute kidney injury after a third surgery was 2.4 times more likely if they had an acute kidney injury after either of the first 2 surgeries . There is a high prevalence of chronic kidney disease in the adult Fontan population with over 50% of patients having reduced glomerular filtration rate or microalbuminuria .…”
Section: Discussionmentioning
confidence: 98%
“…A recent study by Hasson et al looked at a heterogeneous population of pediatric congenital heart disease patients undergoing multiple surgeries. In their cohort, odds of acute kidney injury after a third surgery was 2.4 times more likely if they had an acute kidney injury after either of the first 2 surgeries . There is a high prevalence of chronic kidney disease in the adult Fontan population with over 50% of patients having reduced glomerular filtration rate or microalbuminuria .…”
Section: Discussionmentioning
confidence: 98%
“…The inability to quantify hourly urine output after furosemide may reflect the higher urine flow rate in patients with stage 3 versus stage 2 AKI. It is known that a single episode of AKI lowers the reserve for a subsequent episodes, 19 and increases CKD risk. 20,21 Any efforts to mitigate or reduce the severity of AKI (i.e., avoidance of nephrotoxic medications) 22 could be implemented by assessing urine flow rate following furosemide.…”
Section: Discussionmentioning
confidence: 99%
“…22 Hasson et al were interested in risk factors for recurrent AKI in children undergoing multiple cardiac surgeries. 23 Given the increasing number of children undergoing multiple cardiac surgeries, especially for single ventricle palliation, it is warranted for clinicians to understand the risk factors for adverse outcomes in these children. This was a retrospective study of 180 children younger than 18 years who underwent at least 2 cardiac surgeries, with 89 going on to have a third operation.…”
Section: Acute Kidney Injury In Congenital Cardiac Surgerymentioning
confidence: 99%
“…The investigators found that AKI after the first or second surgery was independently associated with increased relative risk of AKI after a third surgery (2.40 [95% CI ¼ 1.26-4.56]; P ¼ .008). 23 Interestingly, several patients had AKI after surgeries 1 and 3, but not the second surgery. 23 The authors hypothesized that this might be related to a report demonstrating short-term maladaptive hyperfiltration after recurrent AKI.…”
Section: Acute Kidney Injury In Congenital Cardiac Surgerymentioning
confidence: 99%
See 1 more Smart Citation